Vernakularisasi dalam Tafsir Nusantara: Kajian atas Tafsir Faid al-Rahman karya KH. Sholeh Darat al-Samarani - Lilik Faiqoh (Living Islam: Journal of Islamic Discourses, 2018)
This research discusses about vernacularization in Tafsir Nusantara: The Study of Tafsīr Faiḍ al-Raḥmān by KH. Sholeh Darat al-Samarani. There is a Tafsir Nusan- tara which  appears with title of the book is Tafsīr Faiḍ al-Raḥmān fī Tarjamāh Tafsīr Kalām Malik ad-Dayyān by KH. Sholeh Darat al-Samarani who lives in the last of 19th century and in the beginning of 20th  century, as well the first mufassir who writes tafsir that use Javanese language with the alphabet letter of Arabic, the authors are interested to discuss Tafsīr Faiḍ al-Raḥmān. This research raises two form of problems about How vernacularization in Tafsīr Faiḍ al-Raḥmān in terms of language and how vernacularization in Tafsīr Faiḍ al-Raḥmān in terms of interpretation. By using vernacularization theory will be explained that to apply in Tafsīr Faiḍ al-Raḥmān appropriate with vernacularization process in the phenomena of the text which has developed in Tafsīr Faiḍ al-Raḥmān. So, this research can be concluded, first vernacularization in terms of lan- guage include word pengupo jiwo, nyumet damar, and saklas. Vernacularization in terms of language Tafsīr Faiḍ al-Raḥmān more describes about distinctive language of locality that is commonly used by local society. The second, vernacularization in terms of interpretation include Q.S. al-Fātiḥah ([1]: 2), and Q.S. al-Baqarah ([2]: 17), Q.S. al-Baqarah ([2]: 219). Vernacularisation of interpretation in Tafsīr Faiḍ al-Raḥmān more describes about localities’ expression, behaviors and attitudes of Javanese people, the nature of plants in Java and the realms of life in Java.